From Educator to Broader Impacts Professional: A Case Study Analysis of the BI Toolkit Approach - Matthew M. Johnson; Kathleen Hill; Amber Cesare; Tiffany Lewis; Matthew Johnson; Stephanie Klixbull (The University of Alabama, 2024)
Increasing emphasis is being placed by granting agencies on the need for specialists who support the translation of research into societal benefits. This societal benefit is often referred to as broader impacts (BI), and BI is important for acquiring grant funding and fulfilling land-grant university missions, among other benefits. However, few career paths lead directly to becoming a BI professional, so individuals moving into BI work need to transition from another career, which requires learning about BI. This case study examines the experiences of four former classroom teachers making the transition to both teacher educator (a teacher of teachers) and BI professional, and the ways in which their transition was supported using the Center for Advancing Research Impacts in Society (ARIS) BI Toolkit. Implications for onboarding using this toolkit are described and recommendations are made for how to use the ARIS BI Toolkit for transitioning BI professionals.